INFORMATION SERVICES AND PREMARITAL GUIDANCE TO IMPROVE SELF-PREPARATION FOR MARRIAGE (Universitas Islam Negeri Mataram, 2024)
Marriage is the nature of all humans. Wedding preparations need to be understood by individuals and couples because they have an impact, including the desire to live a happy life. Teenagers' inability to control their emotions, make decisions, and understand themselves will make their married life less harmonious. Before marriage occurs, pre-marital information and guidance services are needed to achieve happiness in domestic life. The research aims to determine whether premarital information and guidance services effectively increase self-preparation for marriage. The research uses an experimental research one-group pretest-posttest design. The research subjects were 14 people aged 17 to 18 divided into two groups—sampling using purposive sampling. The instrument used in data collection was the marriage preparation scale. Data analysis uses test statistics. The research results show that there is an influence of premarital information and guidance services on increasing self-preparation for marriage. Furthermore, it was found that premarital guidance was more effective than information services in growing self-preparation of marriage.